2007
DOI: 10.1161/01.res.0000261658.12024.18
|View full text |Cite
|
Sign up to set email alerts
|

Rho Kinase–Mediated Vasoconstriction Is Important in Severe Occlusive Pulmonary Arterial Hypertension in Rats

Abstract: Abstract-Vascular remodeling, rather than vasoconstriction, is believed to account for high vascular resistance in severe pulmonary arterial hypertension (PAH). We have found previously that acute Rho kinase inhibition nearly normalizes PAH in chronically hypoxic rats that have no occlusive neointimal lesions. Here we examined whether Rho kinase-mediated vasoconstriction was also important in a rat model of severe occlusive PAH. Adult rats were exposed to chronic hypoxia (Ϸ10% O 2 ) after subcutaneous injectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
278
2
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 313 publications
(306 citation statements)
references
References 49 publications
20
278
2
2
Order By: Relevance
“…The RhoA/ ROCK pathway is involved in the regulation of a variety of fundamental cell functions (28). Several studies (20,36,37) have demonstrated a critical role for this pathway in the regulation of systemic, pulmonary, and mesenteric vascular tone. Abnormal activation of the RhoA/ROCK pathway has been implicated in the pathogenesis of hypertension by Ca 2ϩ sensitization of the contractile apparatus (28,35,43).…”
Section: Discussionmentioning
confidence: 99%
“…The RhoA/ ROCK pathway is involved in the regulation of a variety of fundamental cell functions (28). Several studies (20,36,37) have demonstrated a critical role for this pathway in the regulation of systemic, pulmonary, and mesenteric vascular tone. Abnormal activation of the RhoA/ROCK pathway has been implicated in the pathogenesis of hypertension by Ca 2ϩ sensitization of the contractile apparatus (28,35,43).…”
Section: Discussionmentioning
confidence: 99%
“…Thirty micrograms of lung tissue protein was used to perform Western blot analysis for SphK1 and SphK2 (Abgent; 1 ∶ 1,000) as described elsewhere. 24 Measurements of pulmonary and cardiac function in PAH rats Echocardiography. Symptoms of PAH in rats were monitored by echocardiography at 4, 8, 10, and 12 weeks after induction of PAH.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…PAH was established in Wistar Kyoto rats by 1 injection (day 0) with SU 5416 (20 mg/kg subcutaneously) in combination with 2 weeks of continuous exposure to hypoxia, followed by 3 weeks in normoxic conditions. 31,32 Hemodynamic measurements RVSP and RV systemic pressure measurements were taken on day 21 before euthanasia, RVH assessment, and tissue harvest. Systemic arterial pressure was recorded via a cannula placed in the carotid artery, as previously described.…”
Section: Disease Modeling In Vivomentioning
confidence: 99%